Comparative analysis of the techniques and tactics of world excellent badminton men`s and women`s doubles - Feng, L.; Chen, T. (Advances in Physical Education, 2023)
Objective: To explore the characteristics of the use of techniques and tactics in world-class women`s and men`s doubles competitions, analyze and summarize the differences and changes in their use of techniques and tactics, and provide reference for the training and competition of Chinese men`s and women`s doubles badminton athletes. Method: This article selected 66 rounds of doubles final videos from 30 international events from 2020 to 2022, and used research methods such as literature review, comparative analysis, and video observation. The results show that: 1) From the perspective of serving and receiving, the main serving points for men`s and women`s doubles are concentrated in position 1, with position 4 as the auxiliary position for men`s doubles and position 6 as the auxiliary position for women`s doubles. The women`s doubles mainly receive and serve by putting the ball, while the men`s doubles combine rubbing and throwing on this basis. 2) In the front court of men`s doubles, the main focus is on throwing the ball, supplemented by pushing and rubbing the ball. In women`s doubles, the main focus is on picking the ball, supplemented by pushing the ball. 3) The men`s doubles mainly draw in the midfield, while the women`s doubles mainly pick the ball. 4) In terms of backcourt skills, women`s doubles use dribbles more frequently than men`s doubles in addition to killing the ball.